Numerical simulation on the dynamic mechanical response and fracture mechanism of rocks containing a single hole - Han, Z; Liu, K; Ma, J; Li, D (SpringerOpen, 2024)
Caverns and tunnels are constantly exposed to dynamic loads, posing a potentially significant threat to the safety of rock structures. To facilitate the understanding of dynamic fracture around openings, a series of discrete element models were established to numerically examine the effect of hole shape on dynamic mechanical properties and crack evolution. The results indicate that the existence of a hole greatly reduces dynamic strength, and the reduction is closely related to hole shape. The strain variation of pre-holed specimens is more complicated and even larger than the value of intact specimens. Although crack initiation differs for varying hole shapes, the entire structural collapse of specimens is controlled by macro shear cracks along the diagonal direction of the specimen, which are effectively identified by velocity trend arrows and contact force distribution. Finally, comparative analysis between failure pattern of pre-holed specimens under static and dynamic loads were conducted.